2019
DOI: 10.1007/s40520-019-01124-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of same-session combined exercise training on cardiorespiratory and functional fitness in older adults: a systematic review and meta-analysis

Abstract: Endurance and strength training are effective strategies for counteracting age-associated reductions in physical performance in older adults, with a combination of both exercise modes recommended to maximise potential fitness benefits. This meta-analysis sought to quantify the effects of same-session combined endurance and strength training on fitness in adults aged over 50 years. Five electronic databases were searched with studies required to include one of the following outcome measures: VO2peak, 6-min walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 105 publications
4
68
0
5
Order By: Relevance
“…Furthermore, improvements in lower body muscle strength may also lead to increase the time to "all-out" on a graded exercise test, increasing the observed VO 2peak [61]. Previous studies have reported that cardiorespiratory fitness is associated with functional capacity and independent living in older adults [58]. We suggest that combined exercise training increases cardiorespiratory fitness, which improves cardiovascular function in older adults.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, improvements in lower body muscle strength may also lead to increase the time to "all-out" on a graded exercise test, increasing the observed VO 2peak [61]. Previous studies have reported that cardiorespiratory fitness is associated with functional capacity and independent living in older adults [58]. We suggest that combined exercise training increases cardiorespiratory fitness, which improves cardiovascular function in older adults.…”
Section: Discussionmentioning
confidence: 70%
“…In the present study, the EXP group showed significantly increased VO 2peak (7.52%) following the 12-week intervention. One meta-analysis reported that a combined exercise program had a moderately positive effect on VO 2peak compared to the control group (3.6 mL·kg −1 ·min −1 ) [58]. In the context of combined training, the inclusion of strength training may provide additional benefits, because previous studies have reported improved cardiorespiratory fitness compatibility after strength training that is potentially mediated by increased mitochondrial enzyme activity and capillary density [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have evaluated the role of exercise on cardiovascular risk factors ( Table 2 ). First, exercise improves cardiorespiratory fitness at different ages [ 68 , 69 ], even in the elderly [ 70 ] and when performed in a reduced-time session of moderate activity [ 71 ].…”
Section: Physical Activity May Narrow the Mortality Gap Of Depressmentioning
confidence: 99%
“…RET aimed at improving muscle strength, endurance or power, defined as any type of muscle strengthening exercise in which participants moved against external resistance (e.g., machinebased weightlifting, free-weight training, rubber bands) (2,3). We also included studies that combined AET and RET with balance or flexibility exercises as complementary training.…”
Section: Eligibility Criteriamentioning
confidence: 99%